2018
DOI: 10.1139/cjp-2017-0620
|View full text |Cite
|
Sign up to set email alerts
|

The role of long relaxation times in a simple model with massless modes

Abstract: The next-nearest-neighbour Ising model with competing nearest-neighbour (nn) and next-nearest-neighbour (nnn) interactions, provides an example of a system in which massless modes destroy order at any finite temperature. This occurs only at a critical ratio, Kc, of the nnn and nn interactions. In this paper we investigate the role of long relaxation times in determining the behaviour of the system when the ratio of the nnn and nn interactions, K, is at and close to this critical ratio. Despite the absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, the physical quantities can not go to the convegence with the kept bond dimension D increasing. There exist a few research about g = 0.5 supporting finite phase transition temperature [42][43][44], but the most claim that the critical temperature is suppressed to zero temperature due to the high degeneracy, just like one-dimensional system [9,11,15,20,21,24]. We put g = 0.5, T c = 0 in the phase diagram.…”
Section: A Phase Diagram and Physical Quantitiesmentioning
confidence: 99%
“…However, the physical quantities can not go to the convegence with the kept bond dimension D increasing. There exist a few research about g = 0.5 supporting finite phase transition temperature [42][43][44], but the most claim that the critical temperature is suppressed to zero temperature due to the high degeneracy, just like one-dimensional system [9,11,15,20,21,24]. We put g = 0.5, T c = 0 in the phase diagram.…”
Section: A Phase Diagram and Physical Quantitiesmentioning
confidence: 99%
“…For κ < 1/2, it has generally been assumed that the transition is part of the Ising universality class, but recent cluster mean-field approximation and effective-field theory study suggest that a narrow first-order transition regime might also be found at κ < ∼ 1/2 [16,17]. Several simulation studies further suggest a nonzero transition temperature at κ = 1/2 proper, i.e., T c (κ = 1/2) > 0 [18,31,32], in marked contrast to prior works [11,[33][34][35][36]. Because theoretical approximations behave irregularly around κ < ∼ 1/2 [37], however, a conclusive assessment has thus far remained out of reach.…”
Section: Introductionmentioning
confidence: 99%